Loss of paraplegin drives spasticity rather than ataxia in a cohort of 241 patients with SPG7. (4th June 2019) - Coarelli, Giulia; Schule, Rebecca; van de Warrenburg, Bart P.C.; De Jonghe, Peter; Ewenczyk, Claire; Martinuzzi, Andrea; Synofzik, Matthis; Hamer, Elisa G.; Baets, Jonathan; Anheim, Mathieu; Schöls, Ludger; Deconinck, Tine; et al.
Abstract : Objective: We took advantage of a large multinational recruitment to delineate genotype-phenotype correlations in a large, trans-European multicenter cohort of patients with spastic paraplegia gene 7 ( SPG7 ). Methods: We analyzed clinical and genetic data from 241 patients with SPG7, integrating neurologic follow-up data. One case was examined neuropathologically. Results: Patients with SPG7 had a mean age of 35.5 ± 14.3 years (n = 233) at onset and presented with spasticity (n = 89), ataxia (n = 74), or both (n = 45). At the first visit, patients with a longer disease duration (>20 years, n = 62) showed more cerebellar dysarthria ( p < 0.05), deep sensory loss ( p < 0.01), muscle wasting ( p < 0.01), ophthalmoplegia ( p < 0.05), and sphincter dysfunction ( p < 0.05) than those with a shorter duration (<10 years, n = 93). Progression, measured by Scale for the Assessment and Rating of Ataxia evaluations, showed a mean annual increase of 1.0 ± 1.4 points in a subgroup of 30 patients. Patients homozygous for loss of function (LOF) variants (n = 65) presented significantly more often with pyramidal signs ( p < 0.05), diminished visual acuity due to optic atrophy ( p < 0.0001), and deep sensory loss ( p < 0.0001) than those with at least 1 missense variant (n = 176). Patients with at least 1 Ala510Val variant (58%) were older (age 37.6 ± 13.7 vs 32.8 ± 14.6 years, p < 0.05) and showed ataxia at onset ( p < 0.05). Neuropathologic examination revealed reduction of the pyramidal tract in the medulla oblongata and moderate loss of Purkinje cells and substantia nigra neurons. Conclusions: This is the largest SPG7 cohort study to date and shows a spasticity-predominant phenotype of LOF variants and more frequent cerebellar ataxia and later onset in patients carrying at least 1 Ala510Val variant.